儒家“個人”的道德身份與道德責任: On the Moral Identity and Moral Responsibility of the Confucian Individual - CAI, Yu (International Journal of Chinese & Comparative Philosophy of Medicine, 2013)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. This article reviews Professor Lo Ping Cheung’s paper, “The Family as the Primary Protector of the Vulnerable: Confucian versus Medical Ethics.” The paper describes human behavior by way of historical narrative, thus offering a historical perspective on philosophical research. His notion of “family co-determination” instead of “parent-determination” also brings a developmental attitude to philosophical research. At the same time, we discuss the moral identity and moral responsibility of the Confucian “individual.” The moral identity of the Confucian “individual” includes both specific cultural identities and a specific social identity. Confucian individuals are the successors, developers and creators of Confucian culture, and also the practitioners and successors of family virtues. These are their moral responsibilities. This article also makes recommendations on forming and expressing family decisions in practice. First, family decisions should be taken by those members of the family who have the capacity to make a decision. However, taking the view of the family as the ethical unit, a family decision should be made on the family’s specific circumstances, with no need for administrative or legal provisions. Second, in accordance with current practice, a representative of the family who has the capacity to make medical decisions should sign an informed consent form. When the views of the patient and his or her family are not consistent, the general principle is that the doctor should follow the patient’s decision. Yet there might be some cases in which the doctor should not follow the decision of the patient; for example, if the patient makes a decision that endangers his or her life due to a lack of knowledge, emotional state or other reasons. In this case, the other family members will put forward their different views based on their responsibility to the patient, and the doctor may comply with the latter. DOWNLOAD HISTORY | This article has been downloaded 301 times in Digital Commons before migrating into this platform.